2007
DOI: 10.1007/s00027-006-0869-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultraviolet and visible radiation on iron lability in boreal and artificial waters

Abstract: Dialysis experiments were used to assess lability of Fe in boreal stream waters as well as synthetic solutions with the chelators ethylenediaminetetraacetic acid (EDTA) and 8-hydroxyquinoline in Bold Basal Medium (BBM). It was hypothesized that irradiation (UV and visible) of organic-Fe complexes would result in enhanced movement of Fe across a dialysis membrane with a 100 Da molecular weight cutoff. Irradiation of boreal stream waters at pH 4 with UV plus visible radiation consistently resulted in increased F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
(47 reference statements)
0
17
0
Order By: Relevance
“…EA-2-2, showing the dominance of colloidal Fe ([ 90%) at the lake's surface). In contrast, in summertime, the photoreaction of Fe(III) under the visible range of light and UV may produce labile (\100 Da) Fe, as shown in experiments on boreal stream waters (Kelton et al 2007). This photoreduction, which was highly variable from 1 year to another and exhibited a diurnal pattern (Emmenegger et al 2001), may partially explain the decrease in colloidal Fe at the expense of LMW forms of Fe in the photic zone (first 4 m) of Lake Maselga that was observed in July 2008 (Fig.…”
Section: Processes In the Water Column Controlling The Colloidal Pattmentioning
confidence: 94%
“…EA-2-2, showing the dominance of colloidal Fe ([ 90%) at the lake's surface). In contrast, in summertime, the photoreaction of Fe(III) under the visible range of light and UV may produce labile (\100 Da) Fe, as shown in experiments on boreal stream waters (Kelton et al 2007). This photoreduction, which was highly variable from 1 year to another and exhibited a diurnal pattern (Emmenegger et al 2001), may partially explain the decrease in colloidal Fe at the expense of LMW forms of Fe in the photic zone (first 4 m) of Lake Maselga that was observed in July 2008 (Fig.…”
Section: Processes In the Water Column Controlling The Colloidal Pattmentioning
confidence: 94%
“…The partitioning of DOC losses between DIC (transferred to the atmosphere) and POC (transferred to the sediments) is controlled in part by acidity which promotes photomineralization to DIC (Dillon and Molot 1997b;Gennings et al 2001;Molot et al 2005) and coagulation by releasing organically bound metals such as Al and Fe (Kopáček et al 2006). The degradation of DOC also releases bound constituents such as P, N (Wang et al 2000;Tarr et al 2001;Vähätalo et al 2003), and metals (e.g., Kopáček et al 2005;Shiller et al 2006;Brooks et al 2007;Kelton et al 2007), thereby increasing their bioavailability.…”
Section: Recommendations and Perspectivesmentioning
confidence: 96%
“…Such knowledge would allow for a better understanding of other climate changedependent effects. Recent work by Kelton (2006) has demonstrated that iron enhances the formation of POC during irradiation of lake water with UV light and therefore may be an important pathway for transfer of allochthonous DOC to sediments. She hypothesized a physical process that excludes any conclusions regarding the chemical alteration of DOC other than removal of adsorbable fractions of DOC by settling amorphous Fe; this process has important implications for the fate of DOC in lakes.…”
Section: Interaction Of Doc With Metals and Nutrientsmentioning
confidence: 99%
“…Particularly, some authors showed that Fe-EDTA is photo-degradable, or that EDTA removal by photooxidation is improved in the presence of iron [56][57][58]. Moreover, EDTA's binding strength is considered as light sensitive for some metals, iron included [59]. On the other hand, EDTA itself is considered as a recalcitrant compound to both biological and chemical processes during sewage treatment [56].…”
Section: Chemicalmentioning
confidence: 99%